Reliability of Contralateral Suppression in Evoked Distortion Product Otoacoustic Emissions - Santos, Ana Carolina dos; Labanca, Ludimila; Assumpção, Larissa Resende; Mancini, Patricia Cotta; Carvalho, Sirley Alves da Silva; Resende, Luciana Macedo de (International Archives of Otorhinolaryngology, 2021)
Introduction Distortion product otoacoustic emissions (DPOAE) and their suppression may be considered useful in monitoring cochlear function and the efferent auditory pathway inhibitory effect. Nonetheless, the establishment of reliable parameters of response variations is of great importance.Objectives To verify the replicability of test and retest in the research of the inhibitory effect of the efferent pathway using contralateral suppressing stimulus during DPOAE recording for clinical applicability.Methods Cross-sectional study with 48 volunteers, aged 18 to 30 years, with normal audiometric thresholds. The procedures included were audiometric and immittance measures to overrule any conductive or sensorineural conditions and DPOAE recordings without and with contralateral suppression with a 60 dBHL white noise. Distortion product otoacoustic emissions amplitudes were analyzed and compared in both conditions with Wilcoxon test, and the Spearman correlation test was used to assess test-retest reliability.Results The comparative analysis showed differences between amplitudes in test and retest conditions only in 1,500 Hz for DPOAE measures with all other tested frequencies showing no differences, and no difference was observed in all recorded frequencies in the test and retest comparison for DPOAE suppression. The degree of correlation between test and retest of DPOAE amplitude was good at 6,000 Hz and strong (r > 0.880) at the other frequencies. For DPOAE with suppression, all frequencies presented strong correlation between test and retest: 1,500 Hz (r = 0.880), 2,000 Hz (r = 0.882), 3,000 Hz (r = 0.940), and 6,000 Hz (r = 0.957).Conclusions The study found good replicability in contralateral suppression of DPOAE with potential clinical applicability, and we recommend conducting the test from 2000Hz to higher frequencies for more reliable results.
Keywords: cochlear hair cells; auditory efferent pathway; reproducibility of results; hearing loss; young adult; noise effects